Assessing the Impact of Common Bile Duct Resection in the Surgical Management of Gallbladder Cancer - GANI, FAIZ (J Surg Oncol, 2016)
BACKGROUND: Although radical re-resection for gallbladder cancer (GBC) has been advocated, the optimal extent of re-resection remains unknown. The current study aimed to assess the impact of common bile duct (CBD) resection on survival among patients undergoing surgery for GBC. METHODS: Patients undergoing curative-intent surgery for GBC were identified using a multi-institutional cohort of patients. Multivariable Cox-proportional hazards regression was performed to identify risk factors for a poor overall survival (OS). RESULTS: Among the 449 patients identified, 26.9% underwent a concomitant CBD resection. The median number of lymph nodes harvested did not differ based on CBD resection (CBD, 4 [IQR: 2–9] vs. no CBD, 3 [IQR: 1–7], P =0.108). While patients who underwent a CBD resection had a worse OS, after adjusting for potential confounders, CBD resection did not impact OS (HR =1.40, 95%CI 0.87–2.27, P =0.170). Rather, the presence of advanced disease (T3: HR =3.11, 95%CI 1.22–7.96, P =0.018; T4: HR =7.24, 95%CI 1.70–30.85, P =0.007) and the presence of disease at the surgical margin (HR =2.58, 95%CI 1.26–5.31, P =0.010) were predictive of a worse OS. CONCLUSIONS: CBD resection did not yield a higher lymph node count and was not associated with an improved survival. Routine CBD excision in the re-resection of GBC is unwarranted and should only be performed selectively.